Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1518/001872001775992499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hearing Protectors on Auditory Localization in Azimuth and Elevation

Abstract: An experiment was conducted to determine the effects of two types of hearing protectors on auditory localization performance. Six listeners localized a 750-ms broadband noise from loudspeakers ranging in azimuth from -180 degrees to +180 degrees and in elevation from -75 degrees to +90 degrees. Independent variables included the type of hearing protector and the elevation of the source. Dependent measures included azimuth error, elevation error, and the percentage of trials resulting in a front-back confusion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 18 publications
(19 reference statements)
2
24
0
1
Order By: Relevance
“…Conventional passive HPDs are necessary as a countermeasure against noise-induced hearing loss in workers, but their use has been shown in a limited number of studies to be detrimental to sound localization in a horizontal plane. [10][11][12][13][14][15][16] As well as investigating the effect of the acoustic features of backup alarm signals on localizing them, it is also important to study the effect of different HPDs, including those that incorporate either passive or electronic augmentations (see Casali [17] for a review), to localize backup alarm signals. This should help industrial safety professionals select HPDs for their workers when localization is an important task and thus a comparison of a wide variety of passive and electronic HPDs was a major focus of the research discussed in this article.…”
Section: Introduction and Literature Backgroundmentioning
confidence: 99%
“…Conventional passive HPDs are necessary as a countermeasure against noise-induced hearing loss in workers, but their use has been shown in a limited number of studies to be detrimental to sound localization in a horizontal plane. [10][11][12][13][14][15][16] As well as investigating the effect of the acoustic features of backup alarm signals on localizing them, it is also important to study the effect of different HPDs, including those that incorporate either passive or electronic augmentations (see Casali [17] for a review), to localize backup alarm signals. This should help industrial safety professionals select HPDs for their workers when localization is an important task and thus a comparison of a wide variety of passive and electronic HPDs was a major focus of the research discussed in this article.…”
Section: Introduction and Literature Backgroundmentioning
confidence: 99%
“…Odbiór dźwięko-wego sygnału bezpieczeństwa jest możliwy jednak wtedy, gdy zostanie on odpowiednio zaprojektowany [4][5][6][7]. Należy także mieć na uwadze, że praca w hałasie o wysokim poziomie często wymaga stosowania ochronników słuchu, co może jeszcze bardziej pogorszyć odbieranie dźwiękowego sygnału bezpieczeństwa [4,[8][9][10][11].…”
Section: Wstępunclassified
“…Both hearing aids and hearing protective devices are reported to degrade sound localization performance ͑Noble et al., 1990;Abel and Armstrong, 1993;Byrne et al, 1998, Vause andGrantham, 1999;Bolia et al, 2001;Brungart et al, 2004;Simpson et al, 2005. Interaural time and level difference cues are the primary cues used for localization of sound in the horizontal plane ͑Blauert, 1997͒.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that many HPDs degrade users' localization ability and affect the acceptability of HPDs ͑Noble et al, 1990;Abel and Armstrong, 1993;Vause and Grantham, 1999;Bolia et al, 2001;Brungart et al, 2004;Simpson et al, 2005͒. A literature search revealed that only a few research studies have examined the effect of directional microphones on hearing aid users' localization performance.…”
Section: Introductionmentioning
confidence: 99%